Pelatihan Kreasi Konten Menarik dalam Media Sosial bagi Pelaku UMKM di Jakarta Utara - Meisyaroh, Siti; Brandinie, Morryessa; Esra, Martha Ayerza; Dasawaty, Elis Sondang (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
In the digital era, social media has become an effective marketing tool for Micro, Small and Medium Enterprises (MSMEs) to increase brand awareness, attract customers and encourage sales. Creating interesting and relevant content is very important so that MSMEs can compete and reach a wider target market. This article discusses various strategies for creating effective social media content for MSMEs, including product promotional content, educational, interactive, behind-the-scenes, viral trends, and customer testimonials. By utilizing these various types of content, MSMEs can build audience engagement, increase credibility and strengthen customer loyalty. The success of a content strategy on social media depends on creativity, consistency, and understanding the needs and preferences of the audience.